333 Targeting the apical intracellular checkpoint CISH unleashes T cell neoantigen reactivity and effector program. (9th November 2020) - Palmer, Douglas; Webber, Beau; Patel, Yogin; Johnson, Matthew; Kariya, Christine; Lahr, Walker; Parkhurst, Maria; Gartner, Jared; Prickett, Todd; Lowery, Frank; Kishton, Rigel; Gurusamy, Devikala; et al.
Abstract : Background: Neoantigen-specific T cells isolated from tumors have shown promise clinically but fail to consistently elicit durable tumor regression. Expression of the intracellular checkpoint CISH is elevated in human tumor infiltrating lymphocytes (TIL) and has been shown to inhibit neoantigen reactivity in murine TIL. Methods: To explore CISH function in human T cells we developed a CRISPR/Cas9-based strategy to knockout (KO) CISH in human T cells with high-efficiency (>90%) and without detectable off-target editing. Results: CISH KO in peripheral blood T cells enhanced proliferation, cytokine polyfunctionality, and cytotoxicity in vitro. To determine if CISH KO similarly enhances TIL function, we developed a clinical-scale, GMP-compliant manufacturing process for CISH disruption in primary human TIL. In process validation runs we achieved CISH KO efficiencies >90% without detectable off-target editing while maintaining high viability and expansion. Compared to WT controls, CISH KO in patient-derived TIL demonstrated increased proliferation, T cell receptor (TCR) avidity, neoantigen recognition, and unmasked reactivity to common p53 mutations. Hyperactivation in CISH KO TIL did not increase differentiation, suggesting that CISH KO may uncouple activation and differentiation pathways. Single cell profiling identifies a pattern of CISH expression inverse to key regulators of activation, and CISH KO in human TIL increases PD1 expression. Adoptive transfer of Cish KO T cells synergistically combines with PD1 inhibition resulting in durable tumor regression in mice, highlighting orthogonal dual cell surface and intracellular checkpoint inhibition as a novel combinatorial approach for T cell immunotherapy. Conclusions: These pre-clinical data offer new insight into neoantigen recognition and serve as the basis for a recently initiated human clinical trial at the University of Minnesota (NCT04426669 ) evaluating inhibition of the novel intracellular immune checkpoint CISH in a CRISPR-engineered, neoantigen-specific T cell therapy for solid tumors. Updates from the clinical trial will be highlighted. Trial Registration: NCT04426669